Dukungan Sosial dan Manajemen Diri pada Lansia Diabetes Melitus Tipe 2 di Komunitas: Dukungan Sosial dan Manajemen Diri pada Lansia Diabetes Melitus Tipe 2 di Komunitas - Arianti, Sindi; Winahyu, Karina Megasari; Hastuti, Hera (Ruang Ide Publisher, 2023)
Diabetes Mellitus is one of the most common metabolic disorders in the world and its percentage tends to increase from year to year. One of the factors to promote a better quality of life is self-care management. Social support is one of the most important factors for improving self-care management. This study aims to identify the description of social support and self-care management in the elderly with type 2 diabetes mellitus in the Mauk Community Health Center, Tangerang Regency. The research design used is a descriptive survey. Data collection used the SDSCA (Summary of Diabetes Self-Care Activities) and MSPSS (Multidimensional Perceived of Social Support) questionnaires which had been tested for validity and reliability. A sample of 167 respondents was taken by purposive sampling technique. The analysis technique used in this study is Univariate. The results of this study indicate that the elderly have social support with an average value of 33.97 and the elderly have self-care management with an average value of 39.11. Conclusions and suggestions, namely family support and self-management of the elderly with Type 2 DM in the moderate range, so it needs to be increased to achieve optimal blood glucose. Keywords: Elderly, Social Support, Self-Management, Type 2 Diabetes Mellitus